IMPLEMENTASI KEBIJAKAN REKRUTMEN TENAGA PENDIDIK TINGKAT SEKOLAH DASAR DI KECAMATAN TELUK MERANTI KABUPATEN PELALAWAN - Hadri "; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Education staff is one of the most important elements in improving the quality of education educators are community members who are devoted and appointed to support the implementation of education, which includes the management of educational units, researchers, civil servants, supervisors, researchers, developers, librarians, laboratory staff and technical technicians. learn. One of the problems that often occurs in the recruitment of educators is the problem of implementing inadequate teaching staff so that there is often irregular acceptance because a lot of work is done in a non-serious manner. Which is the focus of the research on the implementation of teaching staff who are received by the headmaster who does not do as in the acceptance. The Pelalawan district education office has not been maximal in carrying out teaching staff acceptance.This can be seen from the roles of the school principal in carrying out the report after the receipt for the procedure is regulated by the education office but the implementation is carried out by the principal so that many of the teachers in SD Teluk Meranti still have high school diplomas while in law Law No. 74 of 2005 all teaching staff must be S1. The results of the research on teacher recruitment policies in improving the quality of education in SD Meranti sub-district are: (first) the process of receiving teachers in improving the quality of education at Meranti Bay, (second) through the planning of new teacher admissions conducted systematically, organizing by placing appropriate and competent people, standardized structured implementation and supervision carried out during the teacher acceptance process conducted with the aim of improving the quality of education in SD Teluk Meranti (third) the committee always coordinate with all personnel to always emphasize the importance of quality reception so that education at SD Teluk Meranti is increasing. Keywords: Implementation of Educator Recruitment Policy